A case report on the rare presentation of aneurysmal bone cyst on proximal radius with management - Singh, Mohit; Deb, Sudip; Uppal, Sachit; Dagar, Munish; Arunima (International Journal of Research in Orthopaedics, 2023)
Aneurysmal bone cyst (ABC) is a non-neoplastic vaso-cystic tumor of the second decade. A 16-year-old male patient presented to the outpatient department with gradual dull aching pain and progressive increasing swelling, which was localized to right lateral elbow and upper part of the forearm. There was no restriction in the range of motion. After getting an x-ray, a lytic lesion is found at the proximal radius. MRI and cytology, are both investigations done to confirm the diagnosis. Two injections of 10 ml polidocanol (3%) were administered percutaneously two months apart under the guidance of an image intensifier. After one year X-ray showed marked sclerotic, however, the tumor size remained almost the same. Although ABC is a non-aggressive benign lesion. ABC responds to treatment very well. recurrence is also common. Proximal radius is a less common site for ABC and the case report suggests that it is curable. We found no recurrence. Treatment with polidocanol is less expensive, less morbid, has a good functional outcome, early discharge from the hospital, and highly effective.